Internet connectivity disruption in Uruguay (Uruguay) - Voidly (2026)
CRITICAL severity disruption detected in Uruguay. Confidence: 65%. Data sourced from IODA.
Network Disruption Incident ID: UY-2026-0023
Keywords: internet disruption; UY; disruption; critical